2017
DOI: 10.1111/idj.12302
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, diagnosis and management of dentine hypersensitivity: a national survey of dentists in Nigeria

Abstract: Dentists practicing in Nigeria exhibited knowledge gaps concerning DH and its diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…This study evaluated dentists' preferences about the diagnosis and management of DH in addition to their understanding about the type of pain and its predisposing factors. In line with the results of a previous study (92.8%) in Nigeria, 16 a vast majority of participants (85.4%) in this study described DH as a stimulated short sharp pain. It is known that DH is a multifactorial condition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study evaluated dentists' preferences about the diagnosis and management of DH in addition to their understanding about the type of pain and its predisposing factors. In line with the results of a previous study (92.8%) in Nigeria, 16 a vast majority of participants (85.4%) in this study described DH as a stimulated short sharp pain. It is known that DH is a multifactorial condition.…”
Section: Discussionsupporting
confidence: 92%
“…21 Scratching of tooth was the most commonly used diagnostic method reported by dentists in Nigeria. 16 The current study found that many different diagnostic techniques of DH differed significantly between male and female dentists, private and public dentists, and dentists with lesser and greater clinical experience. However, consistent patterns regarding the use of diagnostic methods among these dentists were not identified in the study.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Deve ser dada muita atenção ao diagnóstico desta condição, já que ele é baseado na exclusão de outras condições que apresentam a mesma sintomatologia (21). Além disso, o conhecimento sobre a HD entre a população e até mesmo entre os cirurgiões-dentistas e higienistas ainda é limitado, o que interfere inclusive no diagnóstico e manejo desta condição (15,(22)(23)(24)(25).…”
Section: Introductionunclassified